Micronutrient Daily Intake of Elementary School Children in Bandung as Determined by Using NAA and AAS Methods - E. Damastuti; W.D. Ariyani; M. Santoso; S. Kurniawati; WYN. Syahfitri (PPIKSN-BATAN, 2011)
Micronutrients in human diet are known to be among the most essential sources of nutrition, that required by the human body in small amount to maintain normal physiological function. Micronutrient malnutrition (MNM) is widespread all over the world, mostly in the developing country, where young children tend to be the most at risk of developing micronutrient deficiencies. In Indonesia, data of micronutrient status of children is limited. Therefore, the assessment of micronutrient intake of young children is needed to carry out. Food samples were taken by duplicate diet method of 19 elementary school children in Bandung and were analyzed using neutron activation analysis and atomic absorption spectrophotometry. Quality control of data analysis was assessed using SRM NIST 1548a Typical Diet. The result was giving the average daily intake of Ca, Cr, Cu, Fe, K, Mg, Mn, Na, Se and Zn were 228, 0.15, 0.57, 9.3, 929, 106, 2,1, 2314, 0.022 and 4.6 mg/day respectively and gives 22, 527, 86, 111, 17, 54, 116, 49 and 63% of Recommended Dietary Allowance (RDA) values. Its generally concluded that these children are still lack of micronutrient intake, and many of them were below their recommended dietary allowances. These result were expected could be used as baseline data and reference to encourage government and related institution in making policies for public health improvement and micronutrient malnutrition solution as well. Received: 20 November 2010; Revised: 03 April 2011; Accepted: 04 April 2011